Coefficient Estimates for Certain Subclasses of Bi-Univalent Ma-Minda Mocanu-Convex Functions (Analysis in Theory and Applications, 2014)
In this paper, we introduce and investigate a new subclass of the function class $Σ$ of bi-univalent functions of the Mocanu-convex type defined in the open unit disk, satisfy Ma and Minda subordination conditions. Furthermore, we find estimates on the Taylor-Maclaurin coefficients $|a_2|$ and $|a_3|$ for functions in the new subclass introduced here. Further Application of Hohlov operator to this class is obtained. Several (known or new) consequences of the results are also pointed out.
Keywords: Analytic functions; univalent functions; bi-univalent functions; bi-starlike functions; bi-convex functions; bi-Mocanu-convex functions; subordination; Hohlov operator.